2020
DOI: 10.1007/s11010-020-03777-9
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates angiotensin II-induced cellular hypertrophy through the inhibition of CYP1B1 and the cardiotoxic mid-chain HETE metabolites

Abstract: Several reports demonstrated the direct contribution of cytochrome P450 1B1 (CYP1B1) enzyme and its associated cardiotoxic mid-chain, hydroxyeicosatetraenoic acid (HETEs) metabolites in the development of cardiac hypertrophy. Resveratrol is commercially available polyphenol that exerts beneficial effects in wide array of cardiovascular diseases including cardiac hypertrophy, myocardial infarction and heart failure. Nevertheless, the underlying mechanisms responsible for these effects are not fully elucidated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…As reported for adipokines and myokines, different polyphenolic derivatives regulate natriuretic peptides expression. In in vitro and animal studies, resveratrol mitigates cardiac fibrosis improving anti-inflammatory mechanics and downregulating ANP and BNP gene expression [179]. In the same manner, another antioxidative nutraceutical compound, curcumin alleviates cardiac hypertrophy and decreases ANP and BNP gene expression [180].…”
Section: Natriuretic Peptides: Nutritional Interventionsmentioning
confidence: 99%
“…As reported for adipokines and myokines, different polyphenolic derivatives regulate natriuretic peptides expression. In in vitro and animal studies, resveratrol mitigates cardiac fibrosis improving anti-inflammatory mechanics and downregulating ANP and BNP gene expression [179]. In the same manner, another antioxidative nutraceutical compound, curcumin alleviates cardiac hypertrophy and decreases ANP and BNP gene expression [180].…”
Section: Natriuretic Peptides: Nutritional Interventionsmentioning
confidence: 99%
“… [ 87 , 106 ] 2-methoxyestradiol A biologically active metabolite of estradiol that has been reported to act as a selective CYP1B1 inhibitor and as a strong anti-inflammatory agent. [ 107 , 108 ] …”
Section: Supporting Evidence For the Hypothesismentioning
confidence: 99%
“…Ang II model is a well-established approach to study the AA-mediated alterations in cardiac hypertrophy (Alammari et al, 2020;Shoieb and El-Kadi, 2020;Du et al, 2021;Zhao et al, 2022). The concentration of Ang II used in this study is to mimic the cellular hypertrophic model as previously reported (Shoieb and El-Kadi, 2018;Alammari et al, 2020;Gu et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…Of interest, CYP1As, CYP4As and CYP4Fs are linked to the formation of terminal/subterminal-HETE with CYP1A1 being preferentially oxidizing AA to form 19-HETE and one of the CYPs highest activity (El-Sherbeni and El-Kadi, 2014b). The formation of midchain-HETE is reported to be linked to AA metabolism by CYP1B1 (Shoieb and El-Kadi, 2020;Shoieb et al, 2022). It is worth mentioning that there are differences between CYP1A1 and CYP1B1 enzymes towards metabolizing AA to midchain-HETEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation